Gender-differentiated indicator of nominal rate of protection - a methodology to understand the differentiated impacts of policies on women and men - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Gender-differentiated nominal rates of protection have been successfully calculated for 3 countries: Ethiopia, Malawi, and Uganda.